2014 International Symposium on Computer, Consumer and Control 2014
DOI: 10.1109/is3c.2014.155
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Working Pressure on Structural and Optoelectronic Properties of Al-Doped ZnO Thin Films

Abstract: In this study, we investigated the electrical, optical and structural properties of aluminum-doped ZnO (AZO) thin films by RF magnetron sputtering under different working pressure of 5 -40 mTorr. Optimization of the prepared thin films shows low resistivity of 6.11 × 10 -4 ȍ-cm, mobility of 4.295 cm 2 /V-s and carrier concentration of 3.277 × 10 20 cm -3 at working pressure of 5 mTorr. The maximum transmittance of 98.99 % for wavelengths above 600 nm and Haacke figure of merit (FOM) are 6.44 × 10 -3 ȍ -1 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The value of energy band gap Eg evaluated from the extrapolating linear part of the curve obtain from the graph ℎ 2 versus Photon energy ( ) where the estimated value of band gap value for AZO films is within 3.30 -3.50 range complement the XRD result that only doped ZnO phases that have been successfully deposited onto substrate . The band gap of AZO at lower pressure is broader than higher pressure indicated that as the pressure decreases the AZO films generates a blue shift as the carrier concentration increase [14]. The resistivity values for AZO films by the function of argon pressure are shows in fig 5 . As the argon pressure increase, the resistivity of AZO films also increase implied that the pressure influence the resistivity pattern of AZO films.…”
Section: B Structural Propertiesmentioning
confidence: 96%
“…The value of energy band gap Eg evaluated from the extrapolating linear part of the curve obtain from the graph ℎ 2 versus Photon energy ( ) where the estimated value of band gap value for AZO films is within 3.30 -3.50 range complement the XRD result that only doped ZnO phases that have been successfully deposited onto substrate . The band gap of AZO at lower pressure is broader than higher pressure indicated that as the pressure decreases the AZO films generates a blue shift as the carrier concentration increase [14]. The resistivity values for AZO films by the function of argon pressure are shows in fig 5 . As the argon pressure increase, the resistivity of AZO films also increase implied that the pressure influence the resistivity pattern of AZO films.…”
Section: B Structural Propertiesmentioning
confidence: 96%